Factors associated with hospitalization times and length of stay in patients with bipolar disorder - Shi, Xiaoning; Zhao, Yingying; Yang, Haichen; Xu, Xiufeng; Fang, Yiru; Yu, Xin; Tan, Qingrong; Li, Huichun; Sun, Guangqiang; Wu, Hang; Wang, Pengfei; Yang, Jie; et al. (Frontiers in Psychiatry, 2023)
Aim Appraise the clinical features and influencing factors of the hospitalization times and length of stay in bipolar disorder (BD) patients. Methods This is a multicenter, observational, cohort study of patients diagnosed of type I or type II bipolar disorder. Five hundred twenty outpatients in seven hospitals from six cities in China were recruited from February 2013 to June 2014 and followed up using a continuous sampling pattern. The research included a retrospective period of 12 months and the prospective period of 9 months. The demographic and clinical features of the patients were collected. The influencing factors that could affect the length of stay (number of days spent in the hospital in the prospective period) were analyzed by poisson's regression and the hospitalization times (times of hospitalization in the prospective and retrospective period) was analyzed by general linear model. The selected variables included gender, age, years of education, occupational status, residence status, family history of mental disease, comorbid substance abuse, comorbid anxiety disorder, times of suicide (total suicide times that occurred in the retrospective and prospective period), polarity of the first mood episode, and BD type(I/II). Results Poisson's regression analysis showed that suicide times [Incidence Rate Ratio (IRR) = 1.20, p < 0.001], use of antipsychotic (IRR = 0.62, p = 0.011), and use of antidepressant (IRR = 0.56, p < 0.001) were correlated to more hospitalization times. Linear regression analysis showed that BD type II (β = 0.28, p = 0.005) and unemployment (β = 0.16, p = 0.039) which might mean longer duration of depression and poor function were correlated to longer length of stay. However, patients who experienced more suicide times (β = −0.21, p = 0.007) tended to have a shorter length of stay. Conclusion Overall, better management of the depressive episode and functional rehabilitation may help to reduce the length of stay. BD patients with more hospitalization times were characterized by higher risk of suicide and complex polypharmacy. Patients at high risk of suicide tended to have inadequate therapy and poor compliance, which should be assessed and treated adequately during hospitalization. Clinical trial registration www.ClinicalTrials.gov, Identifier: NCT01770704.